Exploring the impact of oral bacteria remnants on stem cells from the Apical papilla: mineralization potential and inflammatory response - Zymovets, Valeriia; Rakhimova, Olena; Wadelius, Philip; Schmidt, Alexej; Brundin, Malin; Kelk, Peyman; Landström, Maréne; Vestman, Nelly Romani (Frontiers in Cellular and Infection Microbiology, 2023)
Bacterial persistence is considered one of the main causal factors for regenerative endodontic treatment (RET) failure in immature permanent teeth. This interference is claimed to be caused by the interaction of bacteria that reside in the root canal with the stem cells that are one of the essentials for RET. The aim of the study was to investigate whether prolonged exposure of stem cells from the apical papilla (SCAP) to bacterial remnants of Fusobacterium nucleatum, Actinomyces gerensceriae, Slackia exigua, Enterococcus faecalis, Peptostreptococcaceae yurii, commonly found in infected traumatized root canals, and the probiotic bacteria Lactobacillus gasseri and Limosilactobacillus reuteri, can alter SCAP's inflammatory response and mineralization potential. To assess the effect of bacterial remnants on SCAP, we used UV-C–inactivated bacteria (as cell wall-associated virulence factors) and bacterial DNA. Histochemical staining using Osteoimage Mineralization Assay and Alizarin Red analysis was performed to study SCAP mineralization, while inflammatory and osteo/odontogenic-related responses of SCAPs were assessed with Multiplex ELISA. The results showed that mineralization promotion was greater with UV-C–inactivated bacteria compared to bacterial DNA. Immunofluorescence analysis detected that the early mineralization marker alkaline phosphatase (ALP) was increased by the level of E. coli lipopolysaccharide (LPS) positive control in the case of UV-C–inactivated bacteria; meanwhile, DNA treatment decreased the level of ALP compared to the positive control. SCAP’s secretome assessed with Multiplex ELISA showed the upregulation of pro-inflammatory factors IL-6, IL-8, GM-CSF, IL-1β, neurotrophic factor BDNF, and angiogenic factor VEGF, induced by UV-C–killed bacteria. The results suggest that long-term stimulation (for 21 days) of SCAP with UV-C–inactivated bacteria stimulate their mineralization and inflammatory response, while DNA influence has no such effect, which opens up new ideas about the nature of RET failure.